New data on the distribution of Iridana agneshorvathae Collins, Larsen & Sáfián, 2008 with description of the previously unknown female (Lepidoptera, Lycaenidae, Poritiinae) - (:unkn) unknown (My University, 2020)
Recent distribution records of Iridana agneshorvathae (Collins, Larsen & Sáfián 2008), a very rare West African Lycaenida are presented and discussed with description of the previously unknown female. The species is newly recorded from Liberia and Benin showing a significant range extension. The record from Benin is of biogeographic significance as the locality, an isolated forest, is situated in the Dahomey Gap a predominantly savannah habitat, which separates the Upper Guinean forest zone from the Lower Guinean forests. The nocturnal activity of various species of Iridana is also briefly mentioned.
Keywords: African Research